Zinc Oxide Fabrication for Dental Amalgam Strength - Muhammad Uwais Qarni bin Mohd Salleh, Muhammad Uwais Qarni (2011)
Dental amalgam has been used widely as dental restorative material although one of the major components in it is mercury which is well known for its toxicity. Silverfil amalgam produced by Dunia Perwira Manufacturer Sdn. Bhd.which is said to contain no excess mercury.